Characterization of powdered S. japonica as carrier material for natural food preservatives. Issue 1 (1st September 2022) - Putra, Y; Siahaan, E A; Pangestuti, R; Ali, L; Wahab, A
Abstract: S. japonica, an edible brown seaweed, has been used as an efficient biosorbent for its ability in compound adsorption and desorption. Our previous study has demonstrated that natural preservatives (AITC) could be loaded into basic and processed S. japonica via vapor and solution deposition methods. S. japonica carried AITC was successful in inhibiting several foodborne pathogens. According to our previous findings, we proposed this edible brown seaweed suitable for a delivery system of volatile antimicrobials. A comprehensive study was carried out to investigate the absorption and desorption behavior of S. japonica and its porosity. Basic and processed materials of S. japonica were prepared and analyzed. The BET technique was used to determine the surface area and pore size distribution of basic and processed S. japonica . The processed S. japonica powders showed an improvement of pore volume (0.113 cm 3 /g), pore diameter (0.938 nm), and surface area (5.439 m 2 /g); while the basic powders showed dense and smoother surface with smaller pore volume (0.077 cm 3 /g), pore diameter (0.245 nm), and surface area of 0.4529 m 2 /g. It is suggested that the removal of lipid material may contribute to the improvement of pore size distribution.